The co-creation of the functional rating of interaction engagement needs and difficulties scale (FRIENDS) with people with aphasia - Charalambous, Marina; Eftimiou, Stavroulla; Andreou, Elena; Tsiakoulia, Marianna; Phylactou, Phivos (My University, 2025)
Background: Friendship is vital for the well-being and social integration of people with aphasia (PWA) post-stroke. The impact of chronic aphasia on the friendships and social engagement of PWA is often overlooked by rehabilitation clinicians. Aim: To co-create the Functional Rating of Interaction Engagement Needs and Difficulties Scale (FRIENDS), a self-report aphasia-friendly tool, in collaboration with PWA, and test its psychometric properties. Methods: A Patient and Public Involvement approach was adopted, involving 3 PWA and a caregiver as research partners across eight co-design meetings. FRIENDS’ psychometric properties were evaluated with reliability and validity measures. The psychometric study involved 166 participants: 62 PWA, 50 people with stroke without aphasia, and 54 healthy controls. Results: FRIENDS demonstrated excellent internal consistency (Cronbach’s α > 0.960) and high test–retest reliability (ICC ≥0.99). The results demonstrated a significant difference amongst the three groups (p < 0.001), which verified known-groups validity. Significant correlations between FRIENDS and measures of aphasia severity, functional communication, and quality of life supported the tool’s convergent validity. Results derived from analyzing the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) report supported its content validity. Conclusion: FRIENDS is a psychometrically sound, patient-reported outcome measure, developed to rate changes in the friendships of PWA. Co-created with PWA, FRIENDS offers a broad view of chronic aphasia’s impact on friendships, aiding clinicians in co-developing functional intervention plans, enabling person-centered care, and improving the social life of PWA.
Keywords: Aphasia; psychometric testing; co-creation; friendship scale; patient andpublic involvement; stroke